Electrochemical performance and effect of moisture on Ba0.5Sr0.5Sc0.175Nb0.025Co0.8O3-δ oxide as a promising electrode for proton-conducting solid oxide fuel cells. (15th March 2019) - Zhang, Yidan; Zhu, Ankang; Guo, Youmin; Wang, Chunchang; Ni, Meng; Yu, Hao; Zhang, Chuanhui; Shao, Zongping
Graphical abstract: Highlights: Doping Ba 2+ improved phase stability and chemical compatibility of SSNC cathode. Introduced moisture promoted the oxygen reduction reaction of BSSNC cathode. Introduced moisture changed the rate-limiting step of BSSNC cathode. A peak power density of 633 mW cm −2 was obtained with BSSNC cathode at 700 °C. Abstract: Proton conducting solid oxide fuel cells are solid state electrochemical devices for power generation at a conversion efficiency (>60%) higher than conventional thermal power plants (∼40%). The cathode is the key component of proton conducting solid oxide fuel cells as it contributes to more than 50% of the total overpotential loss of an H + -SOFC with thin film electrolyte. This work aims to develop high performance and durable cathode for proton conducting solid oxide fuel cells by doping Ba 2+ into the Sr-site of the SrSc0.175 Nb0.025 Co0.8 O3-δ perovskite oxide. The influence of moisture on the catalytic activity of Ba0.5 Sr0.5 Sc0.175 Nb0.025 Co0.8 O3-δ cathode was investigated using electrochemical impedance spectroscopy of symmetric cell at 600 °C. The resistance in the low-frequency range was found to be the rate-limiting step of the oxygen reduction reaction in the dry air, while the resistance in the medium-frequency range became the rate-limiting step in the moist air. With a Ba0.5 Sr0.5 Sc0.175 Nb0.025 Co0.8 O3-δ cathode, a proton conducting single cell achieved good performance at a temperature of 700 °C with a power density of 633 mW cm −2 . However, the performance of single cell decreased with time, probably due to the agglomeration of cathode particles and the coverage of produced water on the active surface. To improve the durability of the proton conducting solid oxide fuel cell, it is critical to minimize the cathode particle agglomeration and remove the produced water effectively. The research results contribute to the development of high-performance fuel cell for efficient energy conversion.